The Influence of Content Marketing on Purchase Interest Through Brand Image Mediation at Runnie Shop - Sihaloho, Jhonathan; Haryadi, Haryadi (Economic: Journal Economic and Business, 2025)
This study aims to analyze the effect of Content Marketing on Purchase Intention with Brand Image as a mediating variable at Runnie Shop. The research uses a quantitative approach with a sample of 82 respondents selected through purposive sampling, specifically consumers who have previously purchased products from Runnie Shop. The data analysis process is carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, utilizing the SmartPLS version 4 software. The results of the study conclude that Content Marketing has a positive and significant effect on Brand Image and Purchase Intention. Additionally, Brand Image is also proven to have a positive and significant effect on Purchase Intention and mediates the relationship between Content Marketing and Purchase Intention. Therefore, it can be concluded that Content Marketing influences Purchase Intention both directly and indirectly through the mediation of Brand Image at Runnie Shop.